2011
DOI: 10.1002/jbmr.1494
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of 3 versus 6 years of Zoledronic acid treatment of osteoporosis: A randomized extension to the HORIZON-Pivotal Fracture Trial (PFT)

Abstract: Zoledronic acid 5 mg (ZOL) annually for 3 years reduces fracture risk in postmenopausal women with osteoporosis. To investigate long-term effects of ZOL on bone mineral density (BMD) and fracture risk, the Health Outcomes and Reduced Incidence with Zoledronic acid Once Yearly–Pivotal Fracture Trial (HORIZON-PFT) was extended to 6 years. In this international, multicenter, double-blind, placebo-controlled extension trial, 1233 postmenopausal women who received ZOL for 3 years in the core study were randomized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
228
4
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 561 publications
(255 citation statements)
references
References 38 publications
(41 reference statements)
13
228
4
10
Order By: Relevance
“…The study also assessed associations between compliance, baseline covariates and the risks of fracture, fracture-related hospitalization and death in this patient cohort over time. physicians' decisions not to repeat this treatment, perhaps on the basis of evidence which suggests residual antifracture benefits following yearly infusions [32,33]. Similarly, discontinuation of teriparatide may not be indicative of poor medication-taking behaviour as this agent should not be used for more than 24 months over a patient's lifetime [34].…”
Section: Discussionmentioning
confidence: 99%
“…The study also assessed associations between compliance, baseline covariates and the risks of fracture, fracture-related hospitalization and death in this patient cohort over time. physicians' decisions not to repeat this treatment, perhaps on the basis of evidence which suggests residual antifracture benefits following yearly infusions [32,33]. Similarly, discontinuation of teriparatide may not be indicative of poor medication-taking behaviour as this agent should not be used for more than 24 months over a patient's lifetime [34].…”
Section: Discussionmentioning
confidence: 99%
“…This study adjusted the risk between bisphosphonates and stroke. Although bisphosphate use was unrelated to stroke risk in our study, the cardiovascular safety of bisphosphonates for the treatment of osteoporosis remains a concern [29][30][31][32]. Further research on the dosage and course of various bisphosphonates, as well as the risk of stroke after hip fracture and surgery is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term effects on BMD have been reported with 10 and 7 years of continuous treatment with the oral bisphosphonates alendronate [12] and risedronate [13], respectively, and 6 years of IV zoledronate [14]. Similarly, the Monthly Oral iBandronate In LadiEs (MOBILE) study has demonstrated that monthly treatment with 150 mg oral ibandronate provides sustained BMD gains and is well tolerated for up to 5 years in women with postmenopausal osteoporosis [15].…”
Section: Introductionmentioning
confidence: 99%